PENGARUH KETINGGIAN TEMPAT TERHADAP POPULASI SERANGGA PENYERBUK (Elaeidobius kamerunicus Faust) DI KEBUN ADOLINA DAN KEBUN BAH BIRUNG ULU PT. PERKEBUNAN NUSANTARA IV - Nuraida Nuraida; Aulia Juanda; Fajar Nawawi (Institut Teknologi Sawit Indonesia, 2017)
This research aims to know the number of populations of e. kamerunicus in two different heights, to know the comparison population males and females of e. kamerunicus in every height. Based on the results of sampling populations of insect pollinators of e. kamerunicus Palm. Total population sample of e. kamerunicus on Garden Adolina i.e. 2680 tail and on the grounds of ﬂood Birung Ulu i.e. 4548 tail. The sample population average insect e. kamerunicus females i.e. 107 tail on the garden Adolina and 187 tail on the grounds of ﬂood Birung Ulu, and insect populations of e. kamerunicus males i.e. 27 tail on Garden Adolina and 40 tail on the grounds of ﬂood Birung Ulu. The higher the altitude of the place, the higher the average total precipitation per year, and the higher the population of e. kamerunicus